MCYS 2017 PROMOTES COMMUNITY WELL-BEING TO BUILD OUR YOUTH FOR TOMORROW - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
The Multicultural Youth Service (MCYS) 2017 which was held recently in Penang from 5th May – 9th May 2017 was aimed at developing young leaders to ensure the wellbeing of our global human community, and with the mission of helping young people in personal leadership development and peacemaking skills by providing servicelearning opportunities based on the universal principle of living for the sake of others.